2020
DOI: 10.3390/cells9010121
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Fusion Via OPA1 and MFN1 Supports Liver Tumor Cell Metabolism and Growth

Abstract: Metabolic reprogramming universally occurs in cancer. Mitochondria act as the hubs of bioenergetics and metabolism. The morphodynamics of mitochondria, comprised of fusion and fission processes, are closely associated with mitochondrial functions and are often dysregulated in cancer. In this study, we aim to investigate the mitochondrial morphodynamics and its functional consequences in human liver cancer. We observed excessive activation of mitochondrial fusion in tumor tissues from hepatocellular carcinoma (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
66
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 45 publications
5
66
0
Order By: Relevance
“…We have included three batches of healthy human liver organoids and three batches of CC organoids. Because organoids are very difficult to be cultured from HCC tissues, we used liver tumour organoids cultured from CC patients, 18 of which the KARS1 expression levels were shown in Figure 6A. Importantly, similar to what we found in HCC patients, KARS1 expression was significantly higher in patient CC tumour tissues based on the GEPIA database.…”
Section: Resultssupporting
confidence: 62%
“…We have included three batches of healthy human liver organoids and three batches of CC organoids. Because organoids are very difficult to be cultured from HCC tissues, we used liver tumour organoids cultured from CC patients, 18 of which the KARS1 expression levels were shown in Figure 6A. Importantly, similar to what we found in HCC patients, KARS1 expression was significantly higher in patient CC tumour tissues based on the GEPIA database.…”
Section: Resultssupporting
confidence: 62%
“…70 Its overexpression was detected in various tumors including lung cancer 71 and hepatocellular carcinoma. 72 In addition, resistance to chemotherapeutic reagents was demonstrated to be partly stemming from deregulation of OPA1 processing that causes resistance to apoptosis. 73 Our results also suggest OPA1 as a potential oncogene considering its overexpression in HNSC samples.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from its role associated with mitochondria, OPA1 has been reported to modulate apoptosis via controlling cristae junction remodeling, 68,69 to regulate mitochondrial respiration, and mitochondria‐associated cell proliferation 70 . Its overexpression was detected in various tumors including lung cancer 71 and hepatocellular carcinoma 72 . In addition, resistance to chemotherapeutic reagents was demonstrated to be partly stemming from deregulation of OPA1 processing that causes resistance to apoptosis 73 .…”
Section: Discussionmentioning
confidence: 99%
“…Of note, in vitro experiments indicated that MFN1 depletion reprogramed glucose metabolism, eliciting aerobic glycolysis instead of Oxphos. Contrasting results were collected by Li et al, who observed excessive mitochondrial fusion in the tumor tissues of human HCC and in vitro cultured tumor organoids from cholangiocarcinoma [ 41 ]. The knockdown of both MFN1 and OPA1 inhibited mitochondrial fusion in both experimental settings, leading to a reduced cell growth and tumor formation.…”
Section: Fusion and Fission Event In The Onset And Progression Of mentioning
confidence: 98%
“…The knockdown of both MFN1 and OPA1 inhibited mitochondrial fusion in both experimental settings, leading to a reduced cell growth and tumor formation. The authors ascribed the antitumor effect of OPA1 and MFN1 silencing to the induction of pro-apoptotic mechanisms, inhibition of oxidative metabolism, and ATP production [ 41 ]. A realistic speculation might be that the apparently inconsistent observations could be due to the different experimental settings used in these studies.…”
Section: Fusion and Fission Event In The Onset And Progression Of mentioning
confidence: 99%